Shattered on the rock? British financial stability from 1866 to 2007 - Alistair Milne; Geoffrey Wood (Bank of Finland, 2008)
In autumn of 2007 Britain experienced its first bank run of any significance since the reign of Queen Victoria. The run was on a bank called Northern Rock. This was extraordinary, for Britain had been free of such episodes because by early in the third quarter of the 19th century the Bank of England had developed techniques to prevent them. A second extraordinary aspect of the affair was that it was the decision to provide support for the troubled institution that triggered the run. And thirdly, unlike most runs in banking history, it was a run only on that one institution. This paper considers why the traditional techniques for the maintenance of banking stability failed if they did fail and then considers how these techniques may need to be changed or supplemented to prevent such problems in the future. The paper starts with a narrative of the events, then turns to banking policy before the event and to the policy responses after it. We suggest both why the decision to provide support triggered the run and why the run was confined to a single institution. That prepares the way for our consideration of what should be done to help prevent the recurrence of such episodes in the future.
URN:NBN:fi:bof-20140807586
Keywords: 330